Radiofrequency Ablation for Cervical Metastatic Lymph Nodes in Children and Adolescents With Papillary Thyroid Carcinoma: A Preliminary Study - Yan, Lin; Zhang, Ying; Jiang, Bo; Luo, Yukun (Frontiers in Endocrinology, 2021)
Objective To evaluate the safety and efficacy of radiofrequency ablation (RFA) for metastatic lymph nodes (LNs) in children and adolescents with papillary Thyroid Carcinoma (PTC). Materials and Methods From December 2014 to March 2018, 10 metastatic LNs(mean volume 0.30 ± 0.38 ml, range 0.06-1.23ml) in 5 children and adolescents (3 females, 2 males; mean age 15.60 ± 2.97 years, range 12-19 years) with PTC treated by RFA were evaluated in this study. The mean number of surgical procedures performed before RFA was 1.2 (range 1-2) and the mean number of treated metastatic LNs per patient was 2 (rang 1-3). RFA was performed with an 18–gauge bipolar RF applicator under local anesthesia. Follow-up consisted of US and serum thyroglobulin (Tg) level at 1, 3, 6, 12 months and every 12 months thereafter. Results All the patients were well tolerant to RFA procedure and no procedure-related complications occurred. During a mean follow-up time of 52.00 ± 21.44 months, the initial volume of LNs was 0.30 ± 0.38 ml, which significantly decreased to 0.01 ± 0.03 ml (P = 0.005) with a mean VRR of 99.28 ± 2.27%. A total of 9 metastatic LNs (90.00%) completely disappeared. After RFA, 2 patients developed newly metastases. One patient had additional RFA. The other one with multiple LN metastases underwent total thyroidectomy with central neck dissection. Conclusion As a less invasive and effective technique, RFA may provide another alternative to the existing therapeutic modalities for cervical metastatic LNs in children and adolescents with PTC.